EFEKTIFITAS MANAJEMEN PENGGUNAAN LABORATORIUM DALAM PRAKTIKUM BIOLOGI UNIVERSITAS AHMAD DAHLAN - Aris Indriyanti (ITB AAS INDONESIA Surakarta, 2021)
The laboratory is an important facility for education, research, service, quality testing or quality control as well as to support the learning process in schools or universities. The use of laboratories to be effective requires the best management.. This study aims to determine the effectiveness of the use of the Biology laborator. This research is a descriptive quantitative research. This study uses observation techniques, completeness of documents (document study), interviews, and questionnaires in collecting data. The population used in this study were students majoring in Biology education and Biology majoring, Faculty of Mathematics and Natural Sciences UAD, while the samples taken were 82 students by random sampling. The results showed that the use of the Biology laboratory of the Faculty of Mathematics and Natural Sciences UAD in planning practicum activities was in the good category of 67.67%, the use of the biology laboratory was in the good category of 74.7% and the evaluation results of practicum activities were in the good category of 71.01%. The effectiveness of student success in participating in biology practicum is in the effective category with an average overall score of 70.22, The use of good laboratory management and improvement of laboratory facilities and infrastructure are expected to increase the use of laboratories more effectively